Architecture and power in early Central Europe - Graczynska, Marta (Beyond medieval Europe., 2022)
The book presents the panorama of social, cultural, and religious changes in the states of the Piast, Přemyslid, and Arpad dynasties. Major change occurred in the tenth century and again at the turn of the eleventh century. Given the scarcity of written sources, the author employs an analysis of architectural forms which she applies to buildings founded by dukes, kings, and nobles at this period.Architecture serves as a reliable source of knowledge and can be successfully read as a text using comparative analysis, iconology, and semiotics. No piece of art appeared without an historical context.